Deep-sea nematodes (Comesomatidae) from the Southwest Pacific Ocean: five new species and three new species records - Leduc, D. (European Journal of Taxonomy, 2012)
The present study describes five new free-living nematode species and provides three new species records of the family Comesomatidae (genera Cervonema Wieser, 1954, Dorylaimopsis Ditlevsen, 1918, Hopperia Vitiello, 1969, and Kenyanema Muthumbi et al., 1997) from the continental margin of New Zealand, Southwest Pacific. Dichotomous identification keys are provided for all known species of Dorylaimopsis and Hopperia. Cervonema shiae Chen & Vincx, 2000 is recorded for the first time outside the type locality (Beagle Channel, Chile). C. kaikouraensis sp. nov. is characterised by amphideal fovea with 5.5 turns situated at 1.7 head diameter from anterior end, jointed outer labial setae, equal in length to cephalic setae, sperm dimorphism, and 5-6 small pre-cloacal supplements. C. multispira sp. nov. is characterised by amphideal fovea with 8.0-8.5 turns situated at 2.6-4.0 head diameter from anterior end, cephalic setae 2-3 µm long, slightly shorter than outer labial setae, presence of six uninucleated cells in males (potentially pseudocoelomocytes or supplementary excretory cells), 5 small pre-cloacal supplements, and strongly cuticularised, arcuate spicules with capitulum. C. proberti sp. nov. is characterised by amphideal fovea with 5 turns and located at < 1 head diameter from anterior end, cephalic setae 1.6-2.0 times longer than outer labial setae, and 8 small pre-cloacal supplements. Dorylaimopsis nodderi sp. nov. is characterised by cuticle with lateral differentiation consisting of three longitudinal rows of larger dots in the pharyngeal and caudal regions, two rows of larger dots in middle region of body, and spicules with rounded ventral projection at one third of spicule length from distal end, giving appearance of a joint. Hopperia ancora sp. nov. is characterised by short conical cephalic setae, spicules with hook-like projection at distal end, gubernaculum with bent apophyses, and 11-13 pre-cloacal supplements. H. beaglense Chen & Vincx, 1998 is recorded from Kaikoura Canyon, the first record of this species outside the type locality (Beagle Channel, Chile). Kenyanema monorchis Muthumbi et al., 1997 is also recorded for the first time outside the type locality (Indian Ocean).